TRADITIONAL METHOD OF MUNG BEANS (VIGNA RADIATA) PRESERVATION USING PANCHAGAVYA AND ITS EFFECT ON SEED GERMINATION - SWARNALATHA, Y.; SEEMA, SIDDHARTHAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Callosobruchus chinensis is a major pest that affects mung bean causing severe damage during storage. The objective of the present study is aimed to evaluate the effect of panchagavya in larvicidal activity on C. chinensis and its seed germination was observed. Methods: The methods used in this study were followed by observing the people at a remote village in Chittoor district of Andhra Pradesh. This study is about the traditional knowledge of the use of cow urine in panchagavya described in Ayurveda and its application in seed preservation. Results: The ovicidal activity of panchagavya was remarkably good. The ability of ovicidal (instar) development into an adult beetle was found to be nothing. C. chinensis instar and adult beetle showed 100% mortality when treated with cow urine in small concentrations and good seed germination was observed. Conclusion: Panchagavya is potentially effective and eco-friendly in controlling beetles in grains storage and its enhanced seed germination.